Peranan Kinerja Penyuluh Pertanian Terhadap Peningkatan Produktivitas Padi Sawah di Kabupaten Labuhanbatu Utara - Nasution, Fachruddin; Lubis,, Yusniar; Syaifuddin, Syaifuddin (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
Fachruddin Nasution, conducted a study entitled: "The Role of Agricultural Extension Performance with Rice Productivity Improvement in North Labuhan Batu Regency". This study aims to determine the performance of agricultural extension and to analyze the differences in the productivity of paddy in the area between the high-performance extension educator with low performance in North Labuhan Batu Regency. The study used survey methods and implemented in North Labuhan Batu Regency for 3 (three) months, starting in April 2016 s.d. In June, 2016. Total sample of 100 farmers of paddy were divided into 2 groups, for villages with high performance as much as 45 farmers sample while the sample size for the villages with low performance as many as 55 people. The research data were statistically analyzed using analysis of different test average (T test analysis) using SPSS software version19. The results obtained t = 9.006 while find a significance level that is 0,000 less than 0.01 can thus be concluded accept and reject Ho Ha. This means that there are significant differences between the productivity of lowland rice areas of high performance with the performance area extension educator lower at 99% confidence level in the study area.